Discovering retroviruses : beacons in the biosphere - Skalka, Anna Marie (Harvard University Press, 2018)
When invading a host cell, viruses seize cell machinery to make copies of their own genes. The immune system recognizes the invasion. In contrast, retroviruses colonize host cells through the process of reverse transcriptase. Retroviruses open host cell DNA and graft in their retroviral RNA, integrating into the host genome. The immune system has difficulty recognizing or ridding of foreign DNA that has become its own. Discovering Retroviruses presents the history of retrovirus discovery. Skalka illuminates retroviruses' role in evolution, human health, and disease, from the first sighting at the end of the nineteenth century to recent use in genetic engineering. Retroviral sequences in the human genome mark sites where endogenous retrovirus integrated over six million years ago. The 100,000 pieces of retrovirus DNA are remnants from germ line cell invasions and total approximately eight percent of the human genome. Through investigation of animal and human retroviral sequences, we know retroviral mutations can lead to cancers and immunodeficiencies, including HIV and leukemia. Today, researchers harness retroviruses for use in gene delivery systems and precision medicine advances. Discovering Retroviruses offers a lively perspective on stories of the major pioneers of the past century and the extraordinary roads to their discoveries, and demonstrates the growing importance of genetics to modern biomedicine.--